2016
DOI: 10.1039/c6sc00268d
|View full text |Cite|
|
Sign up to set email alerts
|

Structural tuning of organoruthenium compounds allows oxidative switch to control ER stress pathways and bypass multidrug resistance

Abstract: Varying the arene ligand on organoruthenium compounds induced the differential activation of ER stress pathways, leading to non-apoptotic programmed cell death and bypassing drug resistance mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 47 publications
1
70
0
Order By: Relevance
“…Previous work showed that metal-based compounds containing ruthenium could induce endoplasmic reticulum (ER) stress. [32,33] In addition to apoptosis, ER stress can induce autophagy and caspase-independent cell death. [33] To assess the activity of ER stress, we performed Western blot on ATF4 (activating transcription factor 4) (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work showed that metal-based compounds containing ruthenium could induce endoplasmic reticulum (ER) stress. [32,33] In addition to apoptosis, ER stress can induce autophagy and caspase-independent cell death. [33] To assess the activity of ER stress, we performed Western blot on ATF4 (activating transcription factor 4) (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…[32,33] In addition to apoptosis, ER stress can induce autophagy and caspase-independent cell death. [33] To assess the activity of ER stress, we performed Western blot on ATF4 (activating transcription factor 4) (Figure 9). Interestingly, 1·PF 6 strongly induced ATF4 in AGS cells, whereas cisplatin had no effect.…”
Section: Resultsmentioning
confidence: 99%
“…The authors also found that the water-soluble and stable half-sandwich arene Ru(II) Schiff-base (RAS) complexes, 4f and 4g , can induce non-apoptotic programmed cell death (PCD) through the ER stress pathway. 148 The mechanism of action was significantly different between the two complexes, despite modest structural variations. 4g elicited ROS-mediated ER stress, while 4f ’s efficacy was independent of ROS.…”
Section: Arene Ruthenium(ii) Complexesmentioning
confidence: 97%
“…The major mechanism of action proposed for these agents is through the production of reactive oxygen species (ROS). Only a few studies have discovered metal complexes that induce ER stress in the absence of ROS generation . The ability of TRIP to induce ER stress independent of ROS generation indicates that it operates via a different mechanism than many other metallodrugs targeting the ER.…”
Section: Figurementioning
confidence: 99%